2018
DOI: 10.1089/thy.2017.0681
|View full text |Cite
|
Sign up to set email alerts
|

An Online Survey of Hypothyroid Patients Demonstrates Prominent Dissatisfaction

Abstract: A subset of patients with hypothyroidism are not satisfied with their current therapy or their physicians. Higher satisfaction with both treatment and physicians is reported by those patients on DTE. While the study design does not provide a mechanistic explanation for this observation, future studies should investigate whether preference for DTE is related to triiodothyronine levels or other unidentified causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
165
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(173 citation statements)
references
References 48 publications
4
165
0
4
Order By: Relevance
“…In this study, we observed that, among forum participants, 81% perceived as moderate-to-major the effectiveness of DTE therapy. In this regard, our results are similar to previous survey-based studies reporting higher median satisfaction; lower reports of problems with weight management, fatigue, mood, or memory [8]; and an overall positive drug effect in individuals treated with DTE, compared to those taking LT4 or LT4 + LT3 [26]. To the extent of our knowledge, there is only one double-blinded, randomized clinical trial (RCT) evaluating the effectiveness of DTE compared with LT4 in a sample of 70 patients with hypothyroidism [27].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In this study, we observed that, among forum participants, 81% perceived as moderate-to-major the effectiveness of DTE therapy. In this regard, our results are similar to previous survey-based studies reporting higher median satisfaction; lower reports of problems with weight management, fatigue, mood, or memory [8]; and an overall positive drug effect in individuals treated with DTE, compared to those taking LT4 or LT4 + LT3 [26]. To the extent of our knowledge, there is only one double-blinded, randomized clinical trial (RCT) evaluating the effectiveness of DTE compared with LT4 in a sample of 70 patients with hypothyroidism [27].…”
Section: Discussionsupporting
confidence: 90%
“…Nevertheless, there is a concern that, despite the use of LT4 at doses to reach adequate biochemical response, patients often have persistent signs and symptoms of hypothyroidism and low satisfaction with their treatment [6,8]. In this study, we observed that, among forum participants, 81% perceived as moderate-to-major the effectiveness of DTE therapy.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Die 2014 publizierten Leitlinien der American Thyroid Association (ATA) [19] weisen außerdem auf das Fehlen von Langzeitstudien einer Therapie der Hypothyreose mit DTE hin. 2018 ist eine qualitativ anfechtbare Studie zu dem Thema erschienen [29]: es handelt Die andere -viel größere -Studie [31] befragte hypothyreote Patienten, an die sie überdie MitgliederderAmericanThyroid Association herankam, mittels über das Internet ausgesandter umfangreicher Fragebögen nach ihrer Lebensqualität sowie abschließend auch nach der Zufriedenheit mit ihren betreuenden Ärzten. Die Patienten standen entweder unter einer Monotherapie mit L-T4 (n = 6949), oder einer T4/T3-Kombinationstherapie (n = 978) oder einer Therapie mit DTE (n = 3239).…”
Section: Introductionunclassified